Edda Fabbri, Oblivion (Altre Modernità, 2013)
(Oèdipus ed., Salerno/Milano, traduzione e postfazionedi Stefania Mucci, introduzione di Rosa Maria Grillo, 97 pp.ISBN 978-88-734-116-73)di Emilia Perassi